Analisis Konseptual Hutang dan Modal dalam Bisnis Syariah Perspektif Fiqh Muamalah dan Akuntansi Syariah - Ahmad Dzaky Djiloi; A. Amarsyah; Aryandi Aryandi; Masyhuri Masyhuri (INDO PUBLISHING, 2026)
This study analyzes the distinction between debt (qardh) and capital (ra’s al-mal) in Islamic business from a fiqh muamalah perspective and its implications for sharia accounting. Using a qualitative library approach, the study finds that qardh functions as a social contract without profit, while capital is based on partnership and risk sharing linked to real economic activity. In practice, financing is dominated by debt-like and trade-based contracts due to risk and institutional constraints. This creates a gap between normative principles and implementation, especially in risk allocation and contract substance. The study highlights that unclear classification between debt and capital affects financial reporting and weakens accountability. Strengthening conceptual clarity is essential to ensure fairness, transparency, and compliance in sharia accounting.